SUSTAINABILITY APPROACH TO VINEYARD FACILITIES AS TOURISTIC ENTERPRISES: A STUDY IN THRACE - Mehmet Han ERGÜVEN (Fırat University, 2019)
When approached in industrial terms, it is clearly observed in sea-sand-sun (s-s-s) destinations that tourism destroys the nature. Reaching a certain level of satisfaction in s-s-s tourism, the tourists turn towards new tourism types that take form on the basis of “special interests”. Along with the industrial terms, the fact of tourism is also discussed in terms of its geographical extent in these types of tourism. Although it seems like a trendy concept since the 1970s within this context, a concept appears before us, which dates back to 100 years ago especially in Germanic lands: Sustainability. Although sustainability is agreed to have three dimensions, namely socio-ecologic, socio-economic and socio-cultural, only the socio-ecologic aspect is discussed in this study. Total of nine people, who were either owner or the managers of eight out of all 12 Thracian Vineyard Route (TVR) enterprises, have been interviewed in detail in this study by using a qualitative analysis method and the data obtained have been evaluated by descriptive analysis method. Written documents regarding the study has also been reviewed. While conducting the research regarding the vineyard facilities and gastronomy tourism in Thrace, it was revealed that these entrepreneurs were adopting the notion of sustainability. In this study, sustainable entrepreneurship is discussed within the context of its socio-ecologic aspect, under the following subtitles: potable water and waste water, solid waste, energy generation, erosion, contributions to the natural life and habitat and the prudential concerns. Although it was observed that the interviewed entrepreneurs both adopted and tried to practice a sustainable lifestyle in their facilities, it was also observed that some legal procedures were not functional enough to support these efforts.